Prelaminated Supraclavicular Island Flap for Total Ear Reconstruction: A New Technique - Hélio Ricardo Nogueira Alves; Juan Felippe G. U. M. de Rodriguez; Thadeu Rezende Rangel Fernandes; Fábio de Freitas Busnardo; Júlio Morais Besteiro; Cláudio Roberto Cernea; Rolf Gemperli (2020)
Major ear reconstruction has progressed over the past years with the emergence of new techniques directed mainly to patients without available or usable local skin. However, microsurgical transfer requires specific training and eligible patients. The authors report a successful ear reconstruction with a prelaminated supraclavicular island flap in 3 stages, which may be a valuable resource for selected patients or when microsurgery is not available. Advantages and disadvantages of this new technique are discussed, and a possible solution to achieve a more satisfactory result is suggested.